Analyse d’erreurs de l’utilisation des pronoms relatifs qui, que, où et dont chez les étudiants de l’UNIMED - Rahmadhana Fatia Yasmin; Tengku Ratna Soraya (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
Pronouns should be used to avoid repetition and more effectively create French sentences. The 3rd semester students have difficulty using pronouns: Qui, Que, Où, and Dont. This research aims to discover the mistakes in using pronouns such as Qui, Que, Où, and Dont among 3rd-semester students of UNIMED. The research method used in this research is a descriptive qualitative method. The data of this research are 3rd-semester students of UNIMED. The result of the error is relatively high. For pronouns relatives “qui”, they make mistakes as much as 85%. For the relative pronoun “que”, they made mistakes as much as 53%. For the relative pronoun “où” 73%. For the relative pronoun “dont”, they made 85% mistakes. Students lack understanding of the use of all pronoun relatives.